The milk and serum NMR-based metabolic profiles of the South African giraffe (Giraffa camelopardalis giraffa) and their relation to other milk nutrients - Schmidt, Lauren Lorraine (University of the Free State, 2020)
There is little information available on the milk nutrients of wild mammals and none on their milk and serum metabolomes. The giraffe is the largest ruminant and this study compares the information obtained from giraffe with the most common domesticated ruminant, the cow. This is because a lot of information on the cow is available in literature. What makes this study interesting is that the pregnancy status of the female giraffes could be investigated as a variable. The giraffe is one of very few species that can fall pregnant while simultaneously caring for a calf. The current study is part of a larger project regarding behaviour, ecology and biology of giraffes in the Rooipoort Nature Reserve near Kimberley in the Northern Cape. Giraffes were sedated to fit radio transmitters in 2017, and again in 2018 for the removal. Simultaneously, biological samples were collected, inter alia blood and milk. Blood and milk was collected from eleven female giraffes and blood from nine male giraffes. Blood and milk was also obtained from two females in the Sandveld Nature Reserve, Hoopstad district, Free State Province. The metabolites in serum and milk were analysed by Nuclear Magnetic Resonance (NMR) spectroscopy and the milk nutrients (proteins, carbohydrates, fats and fatty acids, and minerals) were analysed according to standard procedures. This study presents a baseline metabolome of serum and milk for giraffes. The results showed differences in serum metabolite concentrations between the 2017 and 2018 samples which could be due to a variation in rainfall and the related availability of browse at the time of collection. The 2018 giraffe group milk metabolite concentrations, particularly lactose, suggest that they were on a lower plain of nutrition when compared to the 2017 giraffe group. The results showed a variation in milk nutrient concentrations between giraffes of different locations and this may be due to different browse being available at these locations because the nutrient content of the browse influences the milk nutrient concentrations. Statistical analysis of milk and serum metabolites showed the greatest differences were between the years of sampling rather than pregnancy status. Pregnancy status was not a significant contribution to the differences in milk nutrients and metabolites. A correlation analysis was used to evaluate the relationship between serum and milk metabolites of female giraffes and their milk nutrients. Milk metabolites were more strongly correlated with milk nutrients than serum metabolites. The serum amino acids isoleucine and valine were positively correlated with milk total protein and casein protein. The milk metabolites alanine, isoleucine, leucine, phenylalanine, and valine were positively correlated with milk whey protein. The serum amino acids isoleucine, leucine, phenylalanine, tyrosine, and valine are all negatively correlated with milk lactose. The concentrations of these amino acids are higher for the 2018 group and the milk lactose concentration is lower for the 2018 group. The lower energy intake for the 2018 group is responsible for the lower lactose concentration and this is correlated with the higher concentrations of serum amino acids because serum amino acids, specifically branched chain amino acids increase in concentrations during starvation. Diet is likely responsible for the positive correlations of milk creatine and creatinine with calcium, iron, lactose, butyric acid, caproic acid, and linoleic acid. Diet affects the concentrations of metabolites and nutrients in milk. Milk citric acid cycle metabolites are positively correlated with lactose. A more energy dense diet, as proposed for the 2017 giraffe group, would lead to an increase in glucose production making more glucose available for lactose production as well as more glucose available to enter the citric acid cycle.
Dissertation (M.Sc. (Microbiology and Biochemistry and Food Biotechnology))--University of the Free State, 2020
Keywords: Giraffe; Giraffa camelopardalis; Milk nutrients; Milk metabolites; Serum metabolites; NMR metabolomics